the Nutritional intervention in anthropometry, biochemical analysis and bioelectrical impedance in adults in the city of Lima, Perú - Apaza Duran, Alan Jimy (2022)
Objective. To determine the effectiveness of nutritional intervention in beneficiaries of soup kitchens in Lima, 2022. Methods. The study was of an applicative type, specifcally pre-experimental design (without control group) and longitudinal cut. The population consisted of all the benefciaries of the soup kitchens of San Luis. The sample consisted of 110 benefciaries of soup kitchens. Results. The nutritional diagnosis changed positively. Regarding the anthropometric evaluation, the median BMI decreased from 27.95 to 26.04; the MAMC decreased from 30.05 to 28.20 and the PAB decreased from 90.00 to 88.00. In relation to biochemical values, median cholesterol level decreased from 190.20 to 184.10; glucose level decreased from 99.30 to 92.40 and hemoglobin level decreased from 13.30 to 13.20. In relation to bioelectrical impedance, the  percentage of fat decreased from 34.00 to 31.00 and the percentage of water increased from 47.00 to 48.00.The p value = 0.00 was less than 0.05; therefore, the change obtained after the nutritional intervention is significant. With respect to hemoglobin the p value = 0.06 was greater than 0.05; therefore, the change was not significant. Conclusions. The nutritional intervention had a significant effect on nutritional status as defned by anthropometry, biochemical analysis and bioelectrical impedance.